General anaesthesia or sedation for percutaneous aortic valve implantation? The questionnaire results and authors’ experience - Kucewicz-Czech, Ewa M. (Kardiochir Torakochirurgia Pol, 2021)
INTRODUCTION: Over the last two decades transcatheter aortic valve replacement (TAVR) has been approved for clinical use. The anaesthetic choice for this procedure is evolving. General anaesthesia was the predominant anaesthetic technique. Growing experience and advances in technology and economic considerations have led to an increasing interest in performing TAVR under monitored sedation. AIM: The assessment of monitored sedation, called cooperative sedation, involves pharmacologically mediated suppression of consciousness and preservation of verbal contact in response to stimulation as a safe method of anaesthesia for TAVR. MATERIAL AND METHODS: Sixty out of 63 TAVR patients with femoral access received monitored sedation. Dexmedetomidine was administered in most of such cases (46 patients). A questionnaire was also carried out by staff involved in performing TAVR procedures, with more than 5 years of experience in it, concerning the method of anaesthesia and perioperative care. RESULTS: Conversion to general anaesthesia was required in 10% of patients (6 cases), only one as a patient-related complication (hypercarbia). The questionnaire carried out showed that anaesthesia and postoperative care after TAVR are underestimated. CONCLUSIONS: The preliminary results regarding anaesthetic management in TAVR procedures demonstrate that monitored sedation is safe, provided that contraindications are observed.